2006
DOI: 10.1007/s10258-006-0007-4
|View full text |Cite
|
Sign up to set email alerts
|

Should employment authorities worry about mergers and acquisitions?

Abstract: Employment, Takeovers, Linked employer–employee data, G34, J21, J23, J31, J63, L29, M51,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…2 Bellak et al (2006) find that foreign takeovers have no causal effect on employment growth among Austrian manufacturing firms. Margolis (2006) reports the negative employment effects of M&As from France, albeit only in the short term.…”
Section: Relevant Empirical Literaturementioning
confidence: 99%
“…2 Bellak et al (2006) find that foreign takeovers have no causal effect on employment growth among Austrian manufacturing firms. Margolis (2006) reports the negative employment effects of M&As from France, albeit only in the short term.…”
Section: Relevant Empirical Literaturementioning
confidence: 99%
“…Devereux and Johnson (2006) had evaluated acquisitions of listed companies in the United Kingdom and had found that these led to job reductions of four percent in the short-run, and over 50 percent in the long-run. Behar and Hodge (2006) have reviewed the record for South African gold mines and had found that mergers led to, on average, one percent employment declines, while Margolis (2006), who had examined French industrial employment, had found that employees of acquired firms are most likely to lose their positions, and have a lower probability of employment with the merged entity, but after three years such distinctions disappear.…”
Section: Mergers Jobs and Wages: The Evidence So Farmentioning
confidence: 99%
“…This view is additionally supported by the case study from Behar & Hodge (2007). Margolis (2006) finds evidence that mergers and acquisitions lead to a reduction in the employment particularly of (comparatively) 'low-skilled' workers, a finding that fits into this line of reason as sclerotic labour markets usually exert an overproportionally adverse effect on low-skilled labour. Altogether, this empirically strengthens the reasoning that countries with persistent involuntary unemployment and sclerotic labour markets experience negative employment effects from increasing merger activity because the employees that lose their job in the course of post-merger rationalisation cannot find a new job.…”
Section: Literature Overviewmentioning
confidence: 77%